PERANAN PERBANKAN SYARIAH DALAM UPAYA PENINGKATAN KESEJAHTERAAN MASYARAKAT - Ikhwanuddin Harahap (Institut Agama Islam Negeri Padangsidimpuan, 2016)
The implementation of sharia banking was already done in some decades ago. It was applied in financial for both productive and consumptive activities. Even the majority of using financial was still for consumptive activites but with the good applied in the future, it will become better. There was a relationship between shariah banking and soceity welfare in a country. It had proved in some country, especially in the country of muslim majority like Malaysia, Saudi Arabia, Sudan and the other. Shariah banking gave a positive impact for the development of economics. There was a forecast said that muslim population will be increase in the future so it will bring an opportunity as well as challenge for shariah banking for improving the products and services also the marketing in order to develop the applied of shariah banking in all aspects of human life. It was in line with the principles of Islam which was support all activities for improving soceity welfare.